Chapter 1, Introduction to contract law and theory - DiMatteo, Larry A. (Principles of Contract Law and Theory, 2023)
This chapter provides background information on the evolution of the common law of contracts. It begins with a short history of the evolution of the common law in England including the roles played by the Roman Catholic Church, the development of a dual court system—one in law and the other in equity, the transition from absolute monarchy to a parliamentary form of government, the creation and restrictiveness of the English writ system, the common law’s reception in America, and the building of a general law of contract in the nineteenth century. It explains the historical differences between law and equity, along with the fusion of the two into a single court system. It also discusses the justifications given for contract law and its role in society. It describes the different perspectives of written or formal law, theory, and practice, and importantly, the difference between law in the books versus law in action. Finally, it explains the differences between rules, principles, and standards, and the boundaries of contract relative to other areas including tort and unjust enrichment.

Business climate and global value chains: Insights from Africa - Ajide, Folorunsho M. (Transnational Corporations Review, 2023)
This paper provides insights on how business climate affect global value chains (GVC) participation in the panel of African nations. The study explores country-level data spanning over a period of 2006–2018. Using the novel method of moments (MM)-Quantile regression, system generalized methods of moments (SYSGMM) and Panel spatial consistent correlation (PSCC) techniques, the study finds that all aspects of business environment have significant impacts on GVC participation in Africa. In specific, information and communication facilities, getting electricity, getting credit, trading across border, enforcing contract, protecting investors and business start-up registration have positive and significant impact on GVC. We also discover that tariff reduces GVC participation while strong political institutions enhance participation. The study concludes that business environment factors are fundamental to ensure high level of GVC participation. Political institutional framework needs to be strengthened to further encourage GVC participation in Africa.
Keywords: Africa; Business environment; Climate; GMM; Global value chains

Terms of trade, governance and household income in selected African countries - Edeme, Richardson Kojo; Mumuni, Sulemana (Sustainable Futures, 2023)
As African countries grapple with the challenges of terms of trade occasioned by economic uncertainty, there is a need for a study on the effect of terms of trade on household income in Africa. Also, as African countries continue to commit to the role of institutional quality in improving terms of trade, this study further reinforces the role of governance on household income in Africa. The study employs the Two-stage Least Squares (2SLS) fixed effects estimation technique based on data spanning 2002–2021 for 36 selected African countries. This study provides more robust evidence by employing household final consumption expenditure as a measure of household income. Findings suggest that improvement in the terms of trade stimulates household income. Similarly, the results indicate that governance plays a critical role in enhancing household income status in Africa. Specifically, government effectiveness, control of corruption, regulatory quality, rule of law, and political stability positively and statistically significantly influence household income levels in Africa. Furthermore, GDP per capita growth positively impacts household income, albeit the effect is statistically insignificant. On the contrary, higher inflation rates, exchange rate volatility, and foreign direct investment (net inflows) have a limiting effect on household income, although, the effect of currency depreciation is generally not statistically significant. Sequel to these findings, the study calls for strong institutional quality and export promotion strategies in Africa.
Keywords: 2SLS; Governance; Household income; Terms of trade

South African controlled foreign companies' rules and the digital economy - Sengwane, Khodani (Potchefstroom Electronic Law Journal, 2023)
South Africa's controlled foreign company ("CFC") rules were enacted more than two decades ago before most of today's business models existed. These are anti-avoidance rules that ensure the South African taxation of profits diverted offshore by South African residents. In terms of the CFC rules, the profits of a non-resident company may also be subject to tax in South Africa at the hands of its South African resident shareholder if such non-resident company is considered to be a CFC. Advances in technology developments and the use of information communication and technology ("ICT") have given rise to what is referred to as the digital economy. The term refers to economic activities hinged on the use of ICT and the internet. Digitalisation has made it possible for a business to carry on economic activity without the need for a multitude of offices, staff, equipment, and other resources. As a result, new business models like Uber and Shien have emerged. This paper argues that the current South African CFC rules have not kept pace with these new business models and do not effectively regulate the new business models and the digital economy. This paper recommends that the CFC rules be updated to address the digital economy and new business models by amending the rules, incorporating the provisions of Electronic Communications and Transactions Act 25 of 2002 into the rules, using country-by-country reporting, and even considering implementing a regime alternative to CFC rules.
Keywords: Anti-avoidance; Controlled foreign company; Deemed source; Digital Economy; Digitalisation; Direct tax; Foreign business establishment exemption

Tacit Choice of Law in International Commercial Contracts. An Analysis of Future Instruments of Developmental Organisations - Bouwers, Garth J. (Potchefstroom Electronic Law Journal, 2023)
This article examines the various regional and supranational organisations of emerging countries that could benefit from a codification of private international law rules. They include the Organisation for the Harmonisation of Business Law in Africa (OHADA), the African Union (AU) and the Association of Southeast Asian Nations (ASEAN). In addition, the article analyses the envisaged instruments that may be especially relevant in the context of the abovementioned organisations. These include the Preliminary Draft Uniform Act on the Law of Obligations in the OHADA Region, the proposed African Principles on the Law Applicable to International Commercial Contracts and the Asian Principles of Private International Law. More specifically, the article focusses on the provisions regarding the determination of the law applicable, particularly those rules relating to a tacit choice of law in international commercial contracts.
Keywords: ASEAN; African Union; Asian Principles of Private International Law; Choice of Law; International Commercial Law; OHADA; Private International Law; Tacit choice of law

The Concise Encyclopedia of Business Ethics - MacDonald, Chris; Marcoux, Alexei (Toronto Metropolitan University, 2023)
The authors’ aim in writing The Concise Encyclopedia of Business Ethics (CEBE) was to provide readers with a useful, concise overview of key issues in business ethics. Our aim is not to be exhaustive, but to provide key definitions, main areas of controversy, and pointers for further reading. It is hoped that it will provide a useful reference guide for students, as well as a starting point for scholars in adjacent fields. Our commitment to sticking to what we consider to be essential topics inevitably means that some readers will find that we have left out what they take to be important topics. For the most part, we stand by our editorial choices. However, as a digital document, it is possible that the CEBE will change and grow slightly over the coming years. Readers are free to provide feedback and suggestions by emailing the authors jointly at editors@bejr.org

Liability in the atmosphere of groups of companies - Motassim, Sofia (Universitat de Barcelona, 2023)
Groups of companies are a complex corporate structure, whose regulation can be problematic, especially when it comes to liability. Indeed, liability within corporate groups draws forth a series of issues principally due to the principles of separate corporate personality and limited liability. In the context of limited liability, which is based on the notion of separate legal personality, the main issue waxes the protection of the creditors, in particular the creditors of the subsidiaries. One can find three regulatory templates for handling corporate groups and their liability: policing via general company and/or civil law (such as the English model); policing via special group legislation (such as the German model); and policing via branches of law such as insolvency law, antitrust law, and contract law, among others (which is the case in numerous jurisdictions, either coupled with the first or the second model). Lifting the corporate veil has come as an answer to corporate separateness, by permitting to ignore the shareholders’ limited liability and hold them personally liable for the debts of their companies in specific circumstances. However, one can hardly find cases in which the corporate veil has been successfully lifted, due to many factors. Other important questions that are posed in the scope of corporate groups liability are the parent company’s liability for the payment of its daughter companies’ debts when insolvency strikes and other respects, besides the matter of group liability. Furthermore, liability is as well a key player in terms of tort law, and corporate social responsibility has therefore found a place in the sun in the present climate.
Keywords: Ciències Jurídiques; Commercial law; Conglomerate corporations; Corporations; Derecho mercantil; Dret mercantil; Econòmiques i Socials; Grupos de empresas; Grups d'empreses; Liability (Law); Responsabilidad (Derecho); Responsabilitat (Dret); Sociedades; Societats

The Autonomy Doctrine in the Law of Letters of Credit and Demand Guarantees in Libya, Egypt and England: A Comparative Study - Mukhtar Elhouderi, Tajeldin Eissa Saleh (University of Leicester, 2023)
Letters of credit and demand guarantees play a prominent role in financing international trade. They provide assurance of payment and security for the performance of contractual obligations and have been described as the ‘lifeblood’ of international commerce. Autonomy is the central principle for the instruments of letters of credit and demand guarantees. Under the autonomy principle, the bank’s undertaking to pay for the beneficiary ought to be independent of the diversity of other relationships arising from the underlying contract. In spite of the autonomous nature of these instruments, in certain cases, the national laws will recognise some exceptions or limitations that restrict the application of the doctrine of autonomy. Exceptions such as fraud, nullity, and illegality will allow the national courts to interfere and override the autonomy doctrine by considering other matters, even those concerning the underlying contract. Furthermore, the exceptions of unconscionability or abuse of rights have an effective role in providing deep solutions, especially with regard to the problem of abusive calls for demand guarantees. The autonomy principle is recognised under Libyan commercial law but has yet to form the subject of serious academic literature covering its legal aspects. This study, in part, aims to fill that gap and will examine the extent to which legal aspects govern the principle of autonomy and its exceptions under Libyan law with reference to the new Libyan Commercial Code. A comparison of the laws in England, Libya, and Egypt will be conducted to examine how legal matters concerning autonomy and its restrictions in their laws are addressed. Furthermore, consideration will be given to the experience of Singapore, particularly with regard to the unconscionability and nullity exceptions. The results of this study will consider many different exceptions to autonomy and suggest that fraud is not the only exception to autonomy and that it is not imperative that all exceptions in letters of credit be equally applied to demand guarantees.
Keywords: Commerce international; Comparative study; Contractual obligations; Egypt; England; International Trade; International commerce; Letter of credit; Letter of guarantee; Lettre de crédit; Lettre de garantie; Libya; Obligation contractuelle

Impact of the Commercial Law on E-Commerce Practices and Business Sustainability in Nigeria - Ufua, Daniel Ebakoleaneh; Olujobi, Olusola Joshua; Al-Faryan, Mamdouh Abdulaziz Saleh (International Journal of Management, Economics and Social Sciences, 2023)
With the advent of global market interdependence and interaction, coupled with the consistent spread of the internet facilities across geographical boundaries, businesses engage in e-commerce practices either to augment existing on-ground businesses or as independent outfits. This study focused on the law on e-commerce practice and business sustainability in Nigeria. The study applied a conceptual review focusing on the trends of development of ecommerce practice and the supportive effects of the legal system in facilitating business sustainability in Nigeria. The study relied on extant literature sourced from various outlets, relevant to the topic of this study. The key findings highlighted and discussed factors for improved e-commerce practices in Nigeria. These included access to legal services, effective government policy and institutional support, time and fair interpretation of the law governing e-commerce, continuous evaluation of the ecommerce processes in Nigeria, increased awareness and familiarity with e-commerce facilities, and the adoption of suitable technology. The study provides valuable insight into the support of the Nigerian commercial sector on e-commerce practices. The adoption of systems theory enhances the promotion of fairness across the entire ambience of e-commerce practice and the support of the law. This implied focusing on the continuous evaluation of legal support and a flexible process of developing the needed approaches to address emerging changes in e-commerce that can enhance business sustainability in Nigeria.
Keywords: Business sustainability; E-commerce; Flexible process; Government Policy; Legal system support; Nigerian economy